Pelestarian Lingkungan Nagari Sibakur Kabupaten Sijunjung: Program Pupuk Kompos sebagai Solusi Sampah Organik - Ali Basrah Pulungan; Aisya Fitri Fadhila; Amanda Triokta Rahmadani; M. Arsyad Hilmi; Patiya Latipah; Ratih Sri Rahayu (CV. ITTC INDONESIA, 2025)
This study examines the implementation of a composting program in Nagari Sibakur, Sijunjung, as a solution for organic waste management. The urgency of this research arises from the increasing volume of unmanaged rural organic waste, which poses environmental challenges. The composting program is an innovative community initiative to reduce waste generation while directly contributing to the SDG of Responsible Consumption and Production. A mixed methodology (observation, interviews, data analysis) was used to collect information. Results are expected to demonstrate that the program has successfully reduced the volume of organic waste, increased the fertility of local agricultural soils, which is crucial for food security, and created additional economic value for the Nagari Sibakur community. This article also analyzes operational and sustainability challenges and identifies strategic opportunities for program development to ensure continued contributions to sustainable development and community well-being.